Beauty out of Chaos: A Parallel Study of Pakistan’s Trauma Art and Literature - Shahzeb Khan, Sahar Hamid* & (Journal of Research in Humanities, 2023)
Employing Tobin Siebers’s notion of “trauma art” from his “The Return to Ritual: Violence and Art in the Media Age”, this paper aims at a parallel examination of the co-presence of beauty and violence in selective works from renowned Pakistani artists like Imran Qureishi and Rashid Rana, and a contemporary Pakistani novel, Bilal Tanweer’s The Scatter Here Is Too Great (2013). Art and writing in Pakistan took a new creative turn as an aftermath of a sequence of events that included 9/11 and widespread terrorism. The contemporary creative realm in Pakistan does not only aspire to discover new arenas with respect to aesthetics, but also delves into issues, which shape and are shaped by questions of culture, nationalism, and self. This paper attempts to investigate violence and its aestheticization in contemporary Pakistani art and fiction and to explore the extent to which it has succeeded in capturing our contemporary cultural scenario. Furthermore, it examines how artists and writers simultaneously challenge this turmoil through creating a thematic binary of hope and resilience. This paper challenges the notion of considering Pakistani art and fiction only a cultural product of our politically electrified and instable state and establishes that it is, simultaneously, a resultant of our richly creative and persevering spirits. Consequently, this study aspires to intrigue researchers interested in similar domains and calls attention to contemporary Pakistani art and literature, encouraging interdisciplinary research.